Analysis of genetic instability induced by radon exposure in iron mine processing workers in Shandong Province, Northern China - Fang, Lianying; Wu, Fangfang; Sun, Hao; Li, Weiguo; Hou, Dianjun; Ma, Ya (Frontiers in Public Health, 2024)
BackgroundRadon, a colorless and odorless radioactive gas, poses serious health risks. It is the second leading cause of lung cancer and notably increases lung cancer risk in smokers. Although previous epidemiological studies have mainly examined lung cancer rates in miners, the effects of radon on genomic stability and its molecular mechanisms are not well understood.MethodsThis study evaluated chromosomal aberrations (CA) and cytokinesis-block micronucleus (CBMN) in miners’ lymphocytes, investigating the relationship between cytogenetic damage and variables such as exposure duration and age. Additionally, gene expression profiles were compared between radon-exposed miners and a control group to identify genes involved in DNA damage repair.ResultsWe observed a significant increase in CA and CBMN among underground miners. Gene expression analysis showed 14 genes were upregulated and four downregulated in the exposed group compared to controls.ConclusionThese findings indicate a strong link between high radon exposure and genomic instability in miners. Improved monitoring of work environments and stronger protective measures are critical to safeguarding miners’ health.